Pengembangan Boneka Kulit Jagung untuk Meningkatkan Kemampuan Berbicara Anak - Sri Wahyuni; Baik Nilawati Astini; I Nyoman Suarta; I Made Suwasa Astawa (Indonesian Journal of Elementary and Childhood Education, 2021)
This research was motivated by the low speaking ability of children aged 5-6 years in the Environment Mujur Village East Praya Subdistrict, Central Lombok Regency. The formulation of the problem is how to form a corn husk doll and how to play it to improve the speaking ability of children aged 5-6 years. The purpose of this research is to find out how to form a corn husk doll and how to play it to improve the speaking ability of children aged 5-6 years in the Environment Mujur Village East Praya Subdistrict, Central Lombok Regency. This type of research is development research with reference to the opinion of Borg & Gall. The research subjects were children aged 5-6 years in the Environment Mujur Village East Praya Subdistrict, Central Lombok Regency which amounted to three children Methods of data collection in this study using the method of observation, and interviews. The data analysis technique in this research was descriptive qualitative. The research used three stages of development with six meetings. Each stage an increase occurs by modifying the tools and materials and the steps of the game. The results obtained at the development stage I (meeting I) obtained a percentage value of (45,83%). there was an increase in stage I (meeting II) by (51,39%), at development stage II (meeting III) it increased again to reach (61,11%), at development stage II (meeting IV) of (68,75%), in development stage III (meeting V) was (75%), development stage III (meeting VI or last) was (86.81%). so, it is highly recommended for parents or teachers to be able to develop media that can improve children's speaking ability, for example, such as corn husk dolls.